Exploring Barrier’s to the implementation of Industrialized Building System (IBS) in residential buildings in Pakistan - Shehr Yar; Muhammad Waheed (PT FORMOSA CENDEKIA GLOBAL, 2023)
A different approach to project construction that is being used by industrialized nations is the adoption of the industrial building system. An industrialized building system is one in which every building component, including slabs, walls, beams and columns, is mass produced in a factory or factory located on the construction site under tight quality control regulations. This study focuses on identifying obstacles to IBS adoption in Pakistani residential buildings. In this research, a questionnaires survey is conducted . The study's conclusions discussed the advantages and difficulties of Pakistan's top-ranked IBS implementation. Furthermore, the report offers recommendations for introducing IBS in Pakistan